2016
DOI: 10.3748/wjg.v22.i34.7813
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of routine duodenal biopsies in iron deficiency anemia

Abstract: AIMTo investigate the cost effectiveness of routine small bowel biopsies (SBBs) in patients with iron deficiency anemia (IDA) independent of their celiac disease (CD) serology test results.METHODSWe used a state transition Markov model. Two strategies were compared: routine SBBs during esophagogastroduodenoscopy (EGD) in all patients with IDA regardless their celiac serology status (strategy A) vs SBBs only in IDA patients with positive serology (strategy B). The main outcomes were quality adjusted life years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Therefore, 6% to 22% of biopsy proven CD cases could be seronegative (2). Performing intestinal biopsy, independently of the CD serology, is also cost efficient in patients with iron-deficiency anemia of unknown origin (35). One study showed that approximately 60% of the physicians are recommending diagnostic intestinal biopsy in patients with CD (9).…”
Section: Cd: Celiac Diseasementioning
confidence: 99%
“…Therefore, 6% to 22% of biopsy proven CD cases could be seronegative (2). Performing intestinal biopsy, independently of the CD serology, is also cost efficient in patients with iron-deficiency anemia of unknown origin (35). One study showed that approximately 60% of the physicians are recommending diagnostic intestinal biopsy in patients with CD (9).…”
Section: Cd: Celiac Diseasementioning
confidence: 99%
“…Grisolano and colleagues reported that its frequency was 8.7% (n=103) 16,17 . Broide, et al have recommended that patients with unexplained iron deficiency anaemia should be worked up for celiac disease by histopathology of biopsies 18 . In our study, 95 (65.5%) patients had unremarkable findings on EGD, but 10 (6.8%) patients were diagnosed as celiac disease on histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have established the need for biopsies in only those with “high‐risk” features but have not categorized anemia into IDA versus non‐IDA, a group in which the incidence of celiac disease is low. Studies have also assessed the role of routine biopsy for IDA, finding a prevalence of celiac disease of around 5–10% in those with documented IDA . In addition, a 2016 cost analysis by Broide et al found that SBBx, regardless of serological status, is cost‐effective in populations in which the prevalence of celiac disease is >5% and, therefore, suggested that all patients with IDA should have SBBx during endoscopy .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also assessed the role of routine biopsy for IDA, finding a prevalence of celiac disease of around 5–10% in those with documented IDA . In addition, a 2016 cost analysis by Broide et al found that SBBx, regardless of serological status, is cost‐effective in populations in which the prevalence of celiac disease is >5% and, therefore, suggested that all patients with IDA should have SBBx during endoscopy . These studies, however, have not combined serological and endoscopic indications for biopsy and have not included demographic features to identify at‐risk populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation